PENGARUH WAKTU INKUBASI DAN JENIS INOKULUM TERHADAP MUTU KEFIR SUSU KAMBING - Galuh Ratmana Hanum (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2016)
Kefir goat milk is fermentation beverage produced by goat milk which had been pasteurization then continued with fermentation used cultur kefir which consist of Lactobacillus acidophilus, Streptococcus lactis and Sacaromyces cereviseae. This research ought to know influence of incubation time and kind of inoculum of quality of kefir goat milk including physical and microbiology qualities. This research factorial design (5x3) are used two way anova and friedman statystic (α=0,05). Result of this research showed that incubation time and kind of inoculums had been influence towards to the chemistry qualities are lactate acid and protein content of kefir goat milk. Incubation time had been influence toward to pH and alcohol content kefir goat milk. While kind of inoculum had not been influence toward to pH and alcohol content kefir goat milk. Incubation time 12 hours with Lactobacillus acidophilus and Streptococcus lactis to produce the best quality of kefir goat milk. Key word : Goat milk, Kefir, Lactobacillus acidophilus, Streptococcus lactis, Sacaromyces cereviseae